HIGH-TEMPERATURE THERMAL-VISION SYSTEM ON THE BASIS OF DIGITAL CAMERA-RECORDER WITH THE PURPOSE OF APPLICATION IN METALLURGY TECHNOLOGIES - I. V. Fain; M. L. German; S. V. Korneev; A. N. Oznobishin (Литьë и металлургия)
The system of measuring of the temperature fields distributing, constructed on the basis of digital camera-recorder, is considered. It is shown that the system has advantages as compared to traditional thermal-imaging sets on receivers, operating in medial and distant infra-red ranges.